Crystal structure of diethyl (E)-2-[(benzofuran-2-yl)methylidene]succinate - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Crystallographic Communications)
The title compound, C 17 H 18 O 5 , was synthesized by a base-free catalytic Wittig reaction. The molecule consists of a diethyl itaconate unit, which is connected via the C=C double bond to a benzofuran moiety. The benzofuran ring system (r.m.s. deviation = 0.007 Å) forms dihedral angles of 79.58 (4) and 12.12 (10)° with the mean planes through the cis and trans ethoxycarbonyl groups, respectively. An intramolecular C—H...O hydrogen bond involving the O atom of the benzofuran moiety is observed. In the crystal, molecules are linked into ribbons running parallel to the b axis by C—H...O hydrogen bonds.
Keywords: T2

Scope and Limitation of the Microwave-Assisted Catalytic Wittig Reaction - Hoffmann, Marcel; Deshmukh, Sunetra; Werner, Thomas (European Journal of Organic Chemistry)
Keywords: T2; CSSD

Recycling of Phosphorus-Based Organocatalysts by Organic Solvent Nanofiltration - Großeheilmann, Julia; Büttner, Hendrik; Kohrt, Christina; Kragl, Udo; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T2; CSSD

Synthesis of Cyclic Carbonates from Epoxides and Carbon Dioxide by Using Bifunctional One-Component Phosphorus-Based Organocatalysts - Büttner, Hendrik; Steinbauer, Johannes; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD

Recyclable Bifunctional Polystyrene and Silica Gel-Supported Organocatalyst for the Coupling of CO2with Epoxides - Kohrt, Christina; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD

Highly Efficient Polymer-Supported Catalytic System for the Valorization of Carbon Dioxide - Desens, Willi; Kohrt, Christina; Frank, Marcus; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD

First Base-Free Catalytic Wittig Reaction - Schirmer, Marie-Luis; Adomeit, Sven; Werner, Thomas (Organic Letters)
Keywords: T2; CSSD

Bifunctional One-Component Catalysts for the Addition of Carbon Dioxide to Epoxides - Büttner, Hendrik; Lau, Kornelia; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: T1; CSSD

Liège, Jean de (1357) - Heinrichs, Ulrike (Allgemeines Künstlerlexikon)

Liège, Jean de - Heinrichs, Ulrike (Allgemeines Künstlerlexikon)

Modelling and simulation of phase transformations in elasto-plastic polycrystals - Ostwald, Richard
Die vorliegende Arbeit behandelt einen neuartigen Modellierungsrahmen zur Simulation von austenitisch-martensitischen Phasentransformationen in Formgedächtnislegierungen (SMA) und TRIP-Stählen. Das Ziel der Arbeit ist die Entwicklung und Ausarbeitung eines generalisierten Modells, welches das charakteristische makroskopische Verhalten sowohl von SMA als auch von TRIP-Stahl abbildet. Als Basis für die Formulierung dient ein skalarwertiges, thermodynamisch konsistentes, auf statistischer Physik basierendes Modell für die Simulation von SMA. Im Verlauf dieser Arbeit wird das Modell in affine und nicht-affine Microsphere-Formulierungen eingebettet um das polykristalline Materialverhalten abzubilden und um die Simulation dreidimensionaler Randwertprobleme zu ermöglichen. Darüberhinaus wird eine Kopplung an Plastizität vorgestellt, welche zusätzlich die Abbildung des Verhaltens von TRIP-Stahl ermöglicht. Abschließend wird die Implementierung eines dreidimensionalen Phasentransformationsmodells für finite Deformationen mit dem Fokus auf repräsentative Transformationsrichtungen in einem thermo-elastoplastischen Framework gezeigt.

An energy-barrier-based computational micro-sphere model for phase-transformations interacting with plasticity - Ostwald, Richard; Bartel, Thorsten; Menzel, Andreas (Computer Methods in Applied Mechanics and Engineering)

A simple one step process for enhancement of titanium foil dye sensitised solar cell anodes - Linnemann, Julia; Giorgio, J.; Wagner, K.; Mathieson, G.; Wallace, G. G.; Officer, D. L. (Journal of Materials Chemistry A)
The photo-conversion efficiency and stability of back-illuminated dye sensitised solar cells with titanium foil based photoanodes are enhanced by a simple nitric acid treatment through which the foil is passivated. This treatment changes the morphology of the titanium foil and increases its electrochemical double layer capacitance.
Keywords: dye sensitized solar cells; DSSCs

Phonon dispersion and zero-point renormalization of LiNbO3 from density-functional perturbation theory - Friedrich, Michael; Riefer, Arthur; Sanna, Simone; Schmidt, Wolf Gero; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
The vibrational properties of stoichiometric LiNbO3 are analyzed within density-functional perturbation theory in order to obtain the complete phonon dispersion of the material. The phonon density of states of the ferroelectric (paraelectric) phase shows two (one) distinct band gaps separating the high-frequency (~800 cm−1) optical branches from the continuum of acoustic and lower optical phonon states. This result leads to specific heat capacites in close agreement with experimental measurements in the range 0–350 K and a Debye temperature of 574 K. The calculated zero-point renormalization of the electronic Kohn–Sham eigenvalues reveals a strong dependence on the phonon wave vectors, especially near Γ. Integrated over all phonon modes, our results indicate a vibrational correction of the electronic band gap of 0.41 eV at 0 K, which is in excellent agreement with the extrapolated temperature-dependent measurements.

Mechanism for nuclear and electron spin excitation by radio frequency current - Müllegger, Stefan; Rauls, Eva; Gerstmann, Uwe; Tebi, Stefano; Serrano, Giulia; Wiespointner-Baumgarthuber, Stefan; Schmidt, Wolf Gero; Koch, Reinhold (Physical Review B)

Interwire coupling forIn(4×1)/Si(111) probed by surface transport - Edler, F.; Miccoli, I.; Demuth, S.; Pfnür, H.; Wippermann, S.; Lücke, A.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Diindenoperylene adsorption on Cu(111) studied with density-functional theory - Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Single PTCDA molecules on planar and stepped KCl and NaCl(100) surfaces - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Barrier-free subsurface incorporation of 3d metal atoms into Bi(111) films - Klein, C.; Vollmers, N. J.; Gerstmann, Uwe; Zahl, P.; Lükermann, D.; Jnawali, G.; Pfnür, H.; Tegenkamp, C.; Sutter, P.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review B)

Modeling atomic force microscopy at LiNbO 3 surfaces from first-principles - Sanna, S.; Dues, C.; Schmidt, Wolf Gero (Computational Materials Science)